'Education is not just teaching': learner thoughts on Exploratory Practice. (1st December 2014) - Hanks, Judith
Abstract: Exploratory Practice (EP) has recently been established as an innovative form of practitioner research in language education, one which includes learners alongside their teachers as co-researchers. However, to date, little attention has been given to learners' perspectives on this approach. This article focuses on the experiences of learners engaging with EP for the first time in an undergraduate English for Academic Purposes context.